PRINCIPLES OF SHARIA WORK ETHIC IN REALIZING AN ETHICAL AND SUSTAINABLE ORGANIZATION - Nurul Pratiwi; Misbahuddin Misbahuddin; Muhammad Nur Taufiq Sunusi (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
This research discusses the principles of the sharia work ethic in realizing an ethical and sustainable organization. In Islam, hard work is not only to achieve material success, but also as an act of worship to Allahswt. and as a responsibility towards Allah swt. Therefore, organizations that want to realize the sharia work ethic must ensure that the work done is halal, sincere, and to meet the needs of the family. This research aims to explore and analyze the principles of Sharia work ethic that are relevant to the creation of an ethical and sustainable organization. This research uses descriptive qualitative research methods through a library research approach. This research shows that the principles of sharia work ethic have an important role in creating an ethical and sustainable organization.